(untitled) (Eurasian Journal of Humanities and Social Sciences, 2025)
Cooperative learning technology is a teaching methodology that organizes the learning process through students working collaboratively in small groups. This method encourages students to work together towards a common goal, fostering active participation in the learning process. In cooperative learning, students are divided into groups where they assist one another, share knowledge, and collectively contribute to overall academic success.